2023
DOI: 10.21315/mjms2023.30.3.6
|View full text |Cite
|
Sign up to set email alerts
|

The Controversial Relationship between Body Mass Index and Handgrip Strength in the Elderly: An Overview

Nadine Soraya,
Edy Parwanto

Abstract: Body mass index (BMI) is one of the most commonly used anthropometric measurements. BMI is measured by dividing an individual’s weight by their height. In the elderly, the aging process causes physiological changes to organ systems as well as body composition. The most noticeable changes occur in the musculoskeletal system—that is, of decreased muscle strength. Handgrip strength is one of the most commonly considered criteria to measure muscle strength. Various factors, including age, gender and anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The obesity paradox indicated that being overweight in the older adult population could decrease mortality by increasing strength and bone mineral density, protecting against falls, and acting as a metabolic reserve during disease [50][51][52]. For older adults, a decrease in BMI was associated with low hand-grip strength [53,54], and some studies suggested that older adults with either lower (<25 kg/m 2 ) or higher BMI (>35 kg/m 2 ) values experience motor deficits [55,56]. Considering the range of BMI (i.e., 18.3-29.8 kg/m 2 ) for older adults in our study, the current findings suggest that decreased BMI is related to fine motor impairments in the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…The obesity paradox indicated that being overweight in the older adult population could decrease mortality by increasing strength and bone mineral density, protecting against falls, and acting as a metabolic reserve during disease [50][51][52]. For older adults, a decrease in BMI was associated with low hand-grip strength [53,54], and some studies suggested that older adults with either lower (<25 kg/m 2 ) or higher BMI (>35 kg/m 2 ) values experience motor deficits [55,56]. Considering the range of BMI (i.e., 18.3-29.8 kg/m 2 ) for older adults in our study, the current findings suggest that decreased BMI is related to fine motor impairments in the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also examined the correlation between anthropometric measures and HGS, but only a few in adolescents. However, the result could have been more conclusive and controversial, so further research is necessary [16] . The different results could occur due to differences in measurement methods and subject characteristics.…”
Section: Discussionmentioning
confidence: 99%